Pengenalan Digitalisasi sebagai modal untuk bersaing dimasa depan di Anak SD 066038, Medan Tuntungan. - Tonny Purba; Berlianti Berlianti; Rida Ningsih Silalahi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Campus Teaching is a learning channel that provides opportunities for students to study off campus for one semester to train their ability to solve complex problems by becoming teacher partners to innovate in learning, develop strategies, and learning models that are creative, innovative, and fun. Through this program, students will be more active in the field and hone their creativity for the sustainability and improvement of the quality of education. For this reason, this journal will explain how the teaching campus program is carried out. The placement in the teaching campus program certainly varies. For this journal, the USU Partners teaching campus program will be explained which was carried out at UPT SD 066038 which is located at Jl. Irrigation No.44, Mangga, Kec. Medan Tuntungan, Medan City, North Sumatra 20131. The focus of the program carried out is the introduction of digitization considering the world and the development of increasingly sophisticated technology. In the introduction of digitization, the method used is group work. Translated with www.DeepL.com/Translator (free version)